Persulfidation is the mechanism underlying sulfide-signaling of autophagy. Issue 3 (4th March 2022) - Gotor, Cecilia; Aroca, Angeles; Romero, Luis C.
ABSTRACT: In this commentary, we highlight the findings described in a recent paper regarding the mechanism of H2 S regulation of macroautophagy/autophagy in mammalian cells and discuss the similarities/divergencies with plant cells. The main outcome is that the posttranslational modification of thiol groups of cysteine residues to form persulfides is a conserved molecular mechanism.